Analysis of asphaltenes and maltenes before and after long-term aging of bitumen. (15th November 2021) - Lu, Xiaohu; Soenen, Hilde; Sjövall, Peter; Pipintakos, Georgios
Highlights: Asphaltenes and maltenes of bitumen before and after aging are investigated chemically. After fractionation more wax is found in the maltenes compared to the bitumen. Maltenes are close to the bitumen, but asphaltenes are more different. Asphaltenes contain low molecular weight molecules that overlap with maltenes. Differences in aromaticity are shown as asphaltenes > bitumen > maltenes. Abstract: Asphaltenes and maltenes of bitumen before and after aging are investigated by differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance spectroscopy ( 1 H NMR), time of flight - secondary ion mass spectrometry (TOF-SIMS), and gel permeation chromatography (GPC). It has been shown that bitumen differs in terms of wax. After fractionation, more wax is found in the maltenes compared to the bitumen, and this is even more evident when bitumen is aged. For one bitumen, asphaltenes from the virgin binder do not contain carbonyls, which all fall into the maltenes. After bitumen aging, a large part of the carbonyl and sulfoxide signals is shifted to the asphaltenes. Differences in aromaticity are also evidenced as asphaltenes > bitumen > maltenes. TOF-SIMS shows that maltenes are close to the bitumen, but asphaltenes are more different. Also, maltenes are relatively unaffected by aging while larger differences are found in the asphaltenes between the virgin and aged binders. By GPC, a large molecular weight fraction of bitumen is shown as main part of the asphaltenes. However, asphaltenes also contain low molecular weight molecules that overlap with maltenes. Upon bitumen aging, some low molecular weight compounds may become part of asphaltenes, making the average molecular weight of the asphaltenes lower.